As inter-relações entre crédito, endividamento, inadimplência e atividade econômica no Brasil entre 2012 e 2018 - Araújo, César Josey de (2019)
This study analyzes the interrelationships between the indicators of credit, indebtedness and economic activity in Brazil during the period from March 2012 to December 2018. The credit variable used expresses that available to individuals with free destination. As well as the others, such as credit portfolio delinquency, household indebtedness, lending, average spread of operations, Selic rate, average term of concessions, economic activity index and unemployment rate, were obtained from official sources such as the Central Bank of Brazil and the Brazilian Institute of Geography and Statistics (IBGE). Estimates from vector autoregressions (VAR) confirm the impact of the unemployment rate on the degree of delinquency, as well as interest rates on the level of indebtedness, as well as proving a vicious cycle of current indebtedness over the future. These results also explain the reduction in lending in the recent period and the persistence of a stagnant national economy, as well as we need public policies to control debt, reduce interest rates or bank spreads and create jobs, in order to stimulate the Brazilian economic growth.